THE CORRELATION BETWEEN THE ANXIETY OF THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM AND THEIR ESSAY WRITING ABILITY - Yogie Alfajar Maisessa; Masyhur Masyhur; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is aimed to find out the correlation between the anxiety of the second year students of English Study Program and their essay writing ability. The sample of this research is one of three classes of the second year students of English Study Program that were chosen by using cluster random sampling technique. The number of sample is 38 students. There were two types of data collected in this research: the data of anxiety and the data of essay writing ability. The anxiety data were gained by using adapted questionnaire from Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz, and Cope. The data of essay writing ability were gained from essay writing test based on the 2013 curriculum. The results show that the anxiety level of population is categorized into “low” level and their essay writing ability is in “good” level. The result revealed that the contribution of anxiety to students’ essay writing ability is 51 %. In conclusion, there is significant correlation between the anxiety of the second year students of English Study Program and their essay writing ability.Key Words: Correlation, Anxiety, Essay Writing Ability